TENUN SAMBAS SEBAGAI WARISAN BUDAYA TAK BENDA (WBTB) DI KABUPATEN SAMBAS, KALIMANTAN BARAT - Agus Dediansyah; Muhammad Sadikin; Basuki Wibowo (Universitas Negeri Yogyakarta, 2021)
AbstractThis study aims to see the history of Sambas weaving from the kingdom to the republic, weaving the identity of the Malay community of Sambas Regency and seeing how the efforts to preserve Sambas weaving by the community and local government of Sambas Regency. This research was conducted using the historical method which consists of the stages of source collection, source criticism, interpretation, and historiography. The results of this study indicate that the history of Sambas weaving cannot be separated from the spread of Islam in the archipelago. The development of Sambas weaving during the Sambas kingdom was so intense and experienced ups and downs during the arrival of the Dutch East Indies and Japanese troops. Weaving as the identity of the Sambas community began to develop and had a market from abroad when it was moved by the Malay community. The identity of Sambas weaving cannot be separated from the characteristics of the Malay community, both in terms of motifs and colors used. The preservation of weaving is carried out in various ways, such as registering as an intangible heritage, establishing a Sambas weaving museum to conducting training training for the younger generation. Keywords: Sambas Weaving